Penerapan Model Pembelajaran Cooperative Integrated Reading And Composition (CIRC) Untuk Meningkatkan Pemahaman Siswa Terhadap Teks Bahasa Arab Pada Siswa Kelas Ix Mts Al Hidayah Kabupaten Tangerang - Saryati, Rasmi (Masterpiece: Journal of Islamic Studies and Social Sciences, 2023)
ABSTRACK This study aims to determine the improvement of Arabic text comprehension skills through the application of the Cooverative Integrated Reading and Compistion model in class IX MTs Al Hidayah Tangerang Regency. The approach of this research is quantitative and the type of research is classroom action research. Classroom action research is a form of research that is reflective in nature by taking certain actions to improve or improve learning practices in the classroom more professionally. It can be concluded that the CIRC method is very helpful for students in understanding Arabic text. In action I, it is known that the number of respondents in the excellent category was 13 respondents 52%, the number of respondents in the good category was 9 respondents 36%, and respondents in the fair category were 3 respondents 12%. And in action II it is known that the number of respondents in the excellent category was 20 respondents 80%, and the number of respondents in the good category was 5 respondents 20%. ABSTRAK Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan pemahaman teks Bahasa Arab melalui penerapan model Cooverative Integrated Reading and Composition di kelas IX MTs Al Hidayah Kabupaten Tangerang. Pendekatan penelitian ini adalah kuantitatif dan jenis penelitian ini adalah penelitian tindakan kelas (Classroom Actoins Research). Penelitian tindakan kelas merupakan suatu bentuk penelitian yang bersifat reflektif dengan melakukan tindakan-tindakan tertentu untuk memperbaiki atau meningkatkan ptaktik-praktik pembelajaran di kelas secara lebih profesional. Dapat disimpulkan bahwa metode CIRC sangat membantu siswa dalam memahami teks Bahasa Arab. Pada tindakan I diketahui bahwa jumlah responden dengan kategori baik sekali sebanyak 13 responden 52%, jumlah responden dengan kategori baik sebanyak 9 responden 36%, dan responden dengan kategori cukup sebanyak 3 responden 12%. Dan pada tindakan II diketahui bahwa jumlah responden dengan kategori baik sekali sebanyak 20 responden 80%, dan jumlah responden dengan kategori baik sebanyak 5 responden 20%.